Novel bioconjugates of aminolevulinic acid with nucleosides - Gurba, Patrice; Vallinayagam, Ramakrishnan; Schmitt, Frederic; Furrer, Julien; Juillerat-Jeanneret, Lucienne; Neier, Reinhard (My University, 2008)
Esters and amino acid derivs. of 5-aminolevulinic acid (ALA) are efficient prodrugs for the prodn. of protoporphyrin IX (PpIX), which has been used in photodynamic cancer therapy (PDT). The synthesis of novel bioconjugates, e.g. I·CF3CO2H, combining ALA with adenosine and thymidine is reported. The novel bioconjugates have been made using a robust methodol. The new class of prodrugs contains one, two, or three ALA per mol. Preliminary cell tests in human cancer cell lines indicate that the thymidine conjugate of ALA is an efficient prodrug for PDT. [on SciFinder(R)]
Keywords: Antitumor agents; Esterification; Human; Neoplasm; Prodrugs (prepn. and anticancer activity of aminolevulinic acid-nucleosides bioconjugates via esterification of nucleosides and aminolevulinic acid derivs.); Nucleosides Role: BPN (Biosynthetic preparation); PAC (Pharmacological activity); RCT (Reactant); SPN (Synthetic preparation); BIOL (Biological study); PREP (Preparation); RACT (Reactant or reagent) (prepn. and anticancer activity of aminolevulinic acid; aminolevulinic acid nucleoside bioconjugate prepn esterification; prodrug anticancer cancer human